Theory, tools, and multidisciplinary applications for tracing groundwater fluxes from temperature profiles. (2nd December 2018) - Kurylyk, Barret L.; Irvine, Dylan J.; Bense, Victor F.
Abstract : Quantifying groundwater fluxes to and from deep aquifers or shallow sediment is a critical task faced by researchers and practitioners from many environmental science disciplines including hydrology, hydrogeology, ecology, climatology, and oceanography. Groundwater discharge to inland and coastal water bodies influences their water budgets, thermal regimes, and biogeochemistry. Conversely, downward water flow from the land surface or from surface water bodies to underlying aquifers represents an important water flux that must be quantified for sustainable groundwater management. Because these vertical subsurface flows are slow and typically diffuse, they cannot be measured directly and must rather be estimated using groundwater tracers. Heat is a naturally occurring groundwater tracer that is ubiquitous in the subsurface and readily measured. Most of the academic literature has focused on groundwater temperature tracing methods capitalizing on the propagation of diel temperature sine waves into sediment beneath surface water bodies. Such methods rely on temperature–time series to infer groundwater fluxes and are typically only viable in the shallow subsurface and in locations with focused groundwater fluxes. Alternative methods that utilize temperature–depth profiles are applicable across a broader range of hydrologic environments, and point‐in‐time measurements can be quickly taken to cover larger spatial scales. Applications of these methods have been impeded due in part to the lack of understanding regarding their potential applications and limitations. Herein, we highlight relevant theory, thermal data collection techniques, and recent diverse field applications to stimulate further multidisciplinary uptake of thermal groundwater tracing methods that rely on temperature–depth profiles. This article is categorized under: Water and Life > Methods Science of Water > Methods Water and Life > Nature of Freshwater Ecosystems Abstract : Diverse environments for using temperature profiles to trace groundwater fluxes. The spatial scales of the temperature profiles and the minimum detectable fluxes, respectively, increase and decrease towards the right. See Figure 1 caption for more details.